2012
DOI: 10.1021/es303303g
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Interactions between Zinc Oxide Nanoparticles and Chlorella sp.

Abstract: The effects of ZnO nanoparticles (NPs) interacting with single-celled green algae, Chlorella sp., have been found to be bilateral. Specifically, our electron microscopy, plant cell, and fluorescence assays showed that the adsorption and aggregation of ZnO NPs compromised algal cell morphology, viability, and membrane integrity, resulting from zinc ion dissolution as well as possible mechanical cell damage induced by the NPs. Conversely, algal cells displayed a remarkable capability of self-protection by minimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 154 publications
(74 citation statements)
references
References 32 publications
2
72
0
Order By: Relevance
“…ZnO NPs are also effective in a range of environmental control technologies from remediation of environmental pollutants to medical disinfection (Hoffmann et al 1995). Chen et al (2012) found that the effects of ZnO NPs interacting with Chlorella sp. to be bilateral, i.e., the adsorption and aggregation of ZnO NPs compromised algal cell morphology, viability, and membrane integrity, resulting from zinc ion dissolution as well as possible mechanical cell damage induced by the NPs.…”
Section: Bioremediation Of Nanoparticles By Algaementioning
confidence: 99%
See 1 more Smart Citation
“…ZnO NPs are also effective in a range of environmental control technologies from remediation of environmental pollutants to medical disinfection (Hoffmann et al 1995). Chen et al (2012) found that the effects of ZnO NPs interacting with Chlorella sp. to be bilateral, i.e., the adsorption and aggregation of ZnO NPs compromised algal cell morphology, viability, and membrane integrity, resulting from zinc ion dissolution as well as possible mechanical cell damage induced by the NPs.…”
Section: Bioremediation Of Nanoparticles By Algaementioning
confidence: 99%
“…Studies conducted on microalgae using ZnO NPs showed this metal oxide to cause growth inhibition of Pseudokirchneriella subcapitata (Franklin et al 2007;Aruoja et al 2009) and Dunaliella teriolecta (Manzo et al 2013); decrease viable cells of Chlorella sp. (Chen et al 2012); depress growth rate of four marine phytoplankton species including Skeletonema marinoi, Thalassiosira pseudonana, Dunaliella teriolecta, and Isochrysis galbana (Miller et al 2010), inhibit photosynthetic activity of Anabaena flos-aquae cyanobacteria and to cause cell death in Euglena gracilis euglenoid microalgae (Brayner et al 2010). Zhou et al (2014) have reported that ZnO NPs were toxic to Chlorella vulgaris and the toxicity was dose-dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Perreault et al studied the effect of polymer coating on copper oxide nanoparticle to green algae, Chlamydomonas reinhardtiiin, with respect to nanoparticle uptake and toxicity, and reported that a high toxicity of polymercoated CuO nanoparticles due to enhancing nanoparticle uptake by algal cells [27]. Chen et al reported that algal cells displayed a remarkable capability of self-protection by minimizing their surface through aggregation mediated by the oppositely charged nano-ZnO particles [28]. Ma et al studied the aggregation of algal cells in the presence of oxide nanoparticles as affected by ionic strength and pH [29].…”
Section: Introductionmentioning
confidence: 99%
“…DOM in the fresh water samples could help to hinder the TiO 2 -cell heteroagglomeration. NPs adhering to and agglomeration with cells would facilitate NP damage to membranes and entrance of cells, as reported for TiO 2 , CNTs, and ZnO NPs with algal cells (Lin et al, 2012b;Long et al, 2012;Zhang et al, 2015;Chen et al, 2012).…”
Section: The Np-cell Heteroagglomeration In the Water Samplesmentioning
confidence: 77%